2021
DOI: 10.1002/hed.26646
|View full text |Cite
|
Sign up to set email alerts
|

Intranodal lymphangiography with thoracic duct embolization for the treatment of chyle leaks after head and neck cancer surgery

Abstract: Background Thoracic duct injury is a rare complication of head and neck surgery. Thoracic duct embolization (TDE) has been proposed to manage postoperative chyle leaks. Methods Twelve patients who underwent lymphangiography for a chyle leak after head and neck surgery (M:F = 5:7, mean 55 years) were retrospectively reviewed. Lymphangiographic findings, technical success, complications, and clinical outcomes were analyzed. Results Chyle leak was identified and TDE attempted in 11 of 12 patients. Three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…The chyle leak was successfully treated with IL guided TDE in all eleven patients in our study, with one case requiring a repeat procedure. Our technical success rate of 92% was similar to the 86% reported by Ushinsky et al in treating chyle leaks after head/neck cancer surgery and superior to other smaller IL TDE studies by Kariya et al and Kim et al which accomplished rates of 75% and 67% respectively [22][23][24]. Our study is the largest series of consecutive IL TDE to treat chyle leaks following thoracic surgery with results comparable to the largest akin study by Nadolski and Itkin which reported a technical success rate of 98% in fifty patients, twenty-two of which had TDE via an IL method [21].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The chyle leak was successfully treated with IL guided TDE in all eleven patients in our study, with one case requiring a repeat procedure. Our technical success rate of 92% was similar to the 86% reported by Ushinsky et al in treating chyle leaks after head/neck cancer surgery and superior to other smaller IL TDE studies by Kariya et al and Kim et al which accomplished rates of 75% and 67% respectively [22][23][24]. Our study is the largest series of consecutive IL TDE to treat chyle leaks following thoracic surgery with results comparable to the largest akin study by Nadolski and Itkin which reported a technical success rate of 98% in fifty patients, twenty-two of which had TDE via an IL method [21].…”
Section: Discussionsupporting
confidence: 87%
“…Our study is the largest series of consecutive IL TDE to treat chyle leaks following thoracic surgery with results comparable to the largest akin study by Nadolski and Itkin which reported a technical success rate of 98% in fifty patients, twenty-two of which had TDE via an IL method [21]. Our overall intention to treat success rate of 92% (11/12) supports IL as an alternative to PL for TDE in the treatment of post-operative chyle leaks, being equivalent to the 75-97% stated in previous PL TDE studies, including the two largest studies by Pamarthi et al in 105 patients and Itkin et al in 106 patients [15,16,17,[20][21][22][23][24]. Our intention to treat rate of 92% is also analogous to the clinical success rates of surgical ligation which ranges from 68% to 90%, with the additional benefits of being minimally [5,7,8,9].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, long-term hospitalization is generally required for recovery. Recently, clinical trials using radiological methods for patients in whom conservative treatments failed have shown favorable outcomes [ 4 , 5 ]; however, these approaches have not been generally established as treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Moon et al [ 1 ] demonstrated that TDE is a safe and effective alternative to surgical treatment. Antegrade thoracic duct access could be used as a first attempt for TDE [ 1 2 3 ]. However, accessing the cisterna chyli is often difficult, and access cannot be achieved in up to 21.4% of cases [ 1 ], especially in patients with obesity or those with small or no cisternal chyli [ 4 ].…”
mentioning
confidence: 99%